Faecal calprotectin levels in children with Henoch–Schönlein purpura. Issue 3 (March 2015) - Kanik, Ali; Baran, Masallah; Ince, Fatma D.; Cebeci, Oksan; Bozkurt, Mehmet; Cavusoglu, Dilek; Eliacik, Kayi; Yavascan, Onder; Helvaci, Mehmet; Aksu, Nejat
<x xml:space="preserve">Abstract</x> Aim We aimed to investigate the significance of faecal calprotectin (FC) levels in children diagnosed with Henoch–Schönlein purpura (HSP) and examine its relationships with gastrointestinal system (GIS), renal involvement and with clinical findings. Patients and methods In total, 66 children diagnosed with HSP for the first time and a control group of 25 healthy children were included. The cases were divided into mild and severe groups on the basis of GIS findings. FC was measured twice in all patients with HSP: within 3 days of onset of disease (FC1) and on day 15 (FC2). These results were compared with those of the control group. Faecal occult blood, gastric wall thickness and duodenal wall thickness were measured at the same time as FC1 in all patients, and the presence of renal involvement was recorded. Results Of the 66 patients, 37 (56%) were females (mean age, 7.5±2.9 years; range, 2.5–14.5 years) and were diagnosed with HSP. Renal involvement was detected in 19 (28%) cases and GIS involvement was found in 28 (43%) cases. GIS involvement was mild in 16 (53%) cases and severe in 12 (43%). A significant difference was detected in FC1 levels between the groups with and without GIS involvement (P=0.01). A marked difference was observed in FC1 levels between the groups with and without renal involvement (P=0.017). Conclusion FC may be a reliable marker for HSP, particularly for identifying GIS and renal involvement as well as disease severity.